Prototype Validity Of Content Learning System (CLS) on Atomic Structure Material Based on Project Based Learning (PjBL) Using Flipped Classroom With Moodle For High School Students In Indonesia - Isramil Husna; Dolla Mulyana Harnas; Fadila Gusman; Elvina Gusman; Setia Erlila Refman Adrus (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2021)
When the Covid-19 epidemic hit Indonesia, one of the learning systems that was suitable for use was learning using e-learning and the use of the blended learning model using the flipped classroom method. This research has been carried out until the validity stage by producing e-learning based on Project Based Learning (PjBL) on Atomic Structure material by applying the flipped classroom approach in the learning process. The type of research is R&D (Research and Development), with a 4-D model consisting of: (1) Define, (2) design, (3) develop, and (4) disseminate. Populations in this research are students from Senior High Shcool in West Sumatera, Indonesia. There are 10 students of SMAN 1 Rambatan, in class X level respondents for developing this product. This products products from the study were validated by 2 chemistry teachers at SMAN 1 Rambatan, The continued at the revision stage based on input from the validator and continued with practicality tests by teachers and students of SMAN 1 Rambatan. Analysis The validity test was carried out using the Cohen kappa formula. Then obtained the kappa value of content validity 0.852 and construct validity 0.737 and from the practicality of teachers and students of 0.709 and 0.742 with very high categories for both very high and high categories. Based on this, it has produced valid and parctical e-learning to be used in the learning process.